Context, Development, and Digital Media: Implications for Very Young Adolescents in LMICs - Magis-Weinberg, Lucía; Ballonoff Suleiman, Ahna; Dahl, Ronald E. (Frontiers in Psychology, 2021)
The rapidly expanding universe of information, media, and learning experiences available through digital technology is creating unique opportunities and vulnerabilities for children and adolescents.These issues are particularly salient during the developmental window at the transition from childhood into adolescence.This period of early adolescence is a time of formative social and emotional learning experiences that can shape identity development in both healthy and unhealthy ways.Increasingly, many of these foundational learning experiences are occurring in on-line digital environments.These expanding vulnerabilities and opportunities are being further amplified for young adolescents growing up in low resourced settings around the world. Cultural and contextual factors influence access, use, and appropriation of digital technology.Further, neurobehavioral changes associated with the onset of puberty often coincide with entry into social media and more autonomous use of technology.In low-and-middle-income countries (LMICs), disparities in access, use, and appropriation of digital media can amplify prevailing economic gaps, and compound gender inequalities during early adolescence. In LMICs, adolescents are often the early adopters of mobile technology and social media platforms. While the impact of social media on the well-being, particularly mental health, of young adolescents has been a focus of research in high-income countries (HICs), much less is known about the impacts of social media use on young adolescents in LMICs. In this paper, we review what is known about the interaction between digital media and early adolescent development. We highlight crucial gaps in the evidence in LMICs; and describe some hypotheses and areas for future research to address these compelling issues